Leydig cell tumor: An unusual presentation - Agrawal Usha (Indian Journal of Pathology and Microbiology, 2009)
Leydig cell tumor is a benign tumor of the testis and malignant transformation, if present, is rare. The case presented here showed certain features of malignancy but no infiltration beyond the capsule or metastasis. The case could not be labeled as benign or malignant and patient is on follow-up. Differential diagnosis and clinical implications of a case in the borderline zone are discussed.